Globalization, Inequality and the Rich Countries of the G-20: Evidence from the Luxembourg Income Study - Timothy Smeeding (Luxembourg Income Study (LIS), 2002)
The purpose of this study is to summarize and comment upon what we know about the determinants of both the level and trend in economic inequality over the past two decades, and to relate these findings to the progress of globalization in these nations. While the fruits of economic progress in rich nations have not been equally spread, we argue that most citizens in rich Organization for Economic Cooperation and Development (OECD) nations have benefited from the trend toward global economic progress. We begin with a summary of the differences in overall economic inequality within the G-20 nations based on LIS (Luxembourg Income Study) data and recent work by others. Here we find that social policies, wage distributions, time worked, social and labor market institutions and demographic differences all have some influence on why there are large differences in inequality among rich nations at any point in time. In contrast, trade policy has not been shown to have any major impact on economic inequality. Next, we turn to trends in inequality. We find modest and sometimes dissimilar changes in the distribution of income have taken place within most advanced nations, with most finding a higher level of inequality in the mid-to-late 1990s than in the 1980s. Inequality, however, has not risen markedly in some nations (e.g., Denmark, Germany, France, and Canada) over this period, while its rise has slowed in several other nations during the late 1990s. The explanations for rising inequality in rich countries are many, and no one single set of explanations is ultimately convincing. In particular, there is no evidence that we know of that trade and globalization is bad for rich countries. This suggests that rising economic inequality is not inevitable, or that it necessarily hurts low skill-low income families. Rather it suggests that globalization does not force any single outcome on any country. Domestic policies and institutions still have large effects on the level and trend of inequality within rich and middle-income nations, even in a globalizing world economy.
Keywords: 330; Einkommensverteilung; Globalisierung; Argentinien; OECD-Staaten; Russland; Brasilien